2022
DOI: 10.1039/d2ra03773d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive separation of para-xylene by nonporous adaptive crystals of phenanthrene[2]arene

Abstract: A new method for the preparation of phenanthrene[2]arene on a large-scale was developed. The synthetic phenanthrene[2]arene has been successfully used as nonporous adaptive crystals for the separation of para-xylene from xylene isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, they optimized the synthesis of precursor 90 in their later work, which was beneficial to the subsequent large-scale production of 91. 90 Crystal structures showed that the dimethoxybenzene subunits connected to the phenanthrene subunits in 91 were twisted to form a rhombicshaped cavity. [6]arene.…”
Section: Leaning Pillarmentioning
confidence: 99%
“…Moreover, they optimized the synthesis of precursor 90 in their later work, which was beneficial to the subsequent large-scale production of 91. 90 Crystal structures showed that the dimethoxybenzene subunits connected to the phenanthrene subunits in 91 were twisted to form a rhombicshaped cavity. [6]arene.…”
Section: Leaning Pillarmentioning
confidence: 99%
“…65 In separate work, Khashab and collaborators developed an efficient adsorptive molecular sieving strategy using crystalline BPTI and showed in particular an effective separation of the MX isomer from an equimolar mixture of xylenes with over 91% fidelity (Figure 8a). 66 The selectivity is attributed to the trianglelike cavity of BPTI, which can capture specific guests 67 Organic cages have also been used for xylene isomer separations. In 2013, Cooper and his team reported that the crystalline porous organic cages CC3 and CC5 could separate xylene isomers based on size and shape specificity.…”
Section: Ethylbenzene Versus Styrenementioning
confidence: 99%
“…The selectivity is attributed to the trianglelike cavity of BPTI , which can capture specific guests (i.e., MX ) based on size/shape-fitting and the effect of multiple C–H···π interactions (Figure b and c). Later in 2022, Hou et al reported another NACs material based on a phenanthrene[2]­arene ( P2A ) macrocycle that allowed separation of PX from the other xylene isomers following the same principle …”
Section: Hydrocarbon Separationsmentioning
confidence: 99%